Da arte ao ofício à produção de um lugar : o Alagamar, Pirambu (SE) - Gonzaga, Taiana Pereira de Almeida (2009)
In the village Alagamar, in Pirambu/SE the handicraft made of the vegetal fiber of ouricuri (Syagrus Coronata) lead the social relations which defines the place and produces a way of life that reflects the ocuppation of being a handicraft maker. This research has as its general ain to study the villager s way of life by enfasazing the social and cultural practices that enable the construction of a singular place the importance of the handicraft to the development of the village as well as the social relations nets based on natural trust and help are the main gorel of this research. Metodologicaly it has based on the concept of Carlos place (1999) and adapt Almeida concepts (2008) about the simbolic territorial dimensions issues. For identification of the social nets the option was Lomnitz s contribuitions (2004) the priorities were qualitative, resources, interviemes, informal talk, observation of the relity and photos. Key actors fron the village and representatives from the institutions involved in the handicraft manufecture were interviewed, the final considations are about how the way of life in this village is affected by the fases of its productions and commerce of the handicraft which directly affects peoples life the obsorved social relations are also defined by the handicraft activities and the mainnets are classifield as: strong, fragile, weok and emergent, these were defined fron trust and family ties among their participants. SEBRAE har started the handicraft activity in Alagamar, but the lack pf public policy has been harmful to the devepment of this place. It s necessary for the local and state government to pronote actions that encreases the hamdicraft in the village as well as the qualifications inprovenent of those who criate the handicraft the handicraft makers.